2014
DOI: 10.29252/jnkums.6.3.573
|View full text |Cite
|
Sign up to set email alerts
|

Race of apparent abnormalities in neonates born in Amir-Almomenin hospital of Sistan

Abstract: Background & Objectives: Congenital abnormalities are essential causes of morbidity and mortality in neonates. Congenital disorders are diseases which develop during egg fertilization or during embryo development. The prevalence of affected infants that are born alive is estimated about 3-5%. .This study has been performed on revealed malformations of the infants born in Sistan region. Material & Methods: This descriptive cross-sectional analysis was performed on all infants born alive and the congenital anoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Khoshhal-Rahdar et al (24) and Alijahan et al (25) found musculoskeletal anomalies as the most common congenital defects. In the Hosseini et al (26) study, anomalies of eye, ear and face ranked first followed by nervous system disorders. According to Jalali et al (23), the most and the least prevalent congenital anomalies were respectively linked to musculoskeletal and genitourinary abnormalities.…”
Section: Discussionmentioning
confidence: 98%
“…Khoshhal-Rahdar et al (24) and Alijahan et al (25) found musculoskeletal anomalies as the most common congenital defects. In the Hosseini et al (26) study, anomalies of eye, ear and face ranked first followed by nervous system disorders. According to Jalali et al (23), the most and the least prevalent congenital anomalies were respectively linked to musculoskeletal and genitourinary abnormalities.…”
Section: Discussionmentioning
confidence: 98%
“…Families in low-income countries have less access to health services and are deprived of access to health care due to financial problems or lack of services [8,9]. For example, Zahari et al indicated that the prevalence of congenital heart diseases in people with DS is similar in Malaysia and high-income countries, but the survival rate was lower in this country because of the delay in performing required medical surgeries due to limited human and physical resources [10].…”
Section: Discussionmentioning
confidence: 99%
“…The center for disease control and prevention also reported that around 3% of all births in the United States are affected by CAs (20). Studies in Iran also showed that the prevalence of major CAs in Tehran was 18 cases per 1000 births (6), while the prevalence of obvious major CAs per 1000 births was 8.5 -17 cases among different ethnic groups in Gorgan (9), 8.2 cases in Ardebil (10), 8.92 -2046 cases in different areas of Golestan province (21), and 18 cases in Sistan (22). The CA prevalence in an earlier study in Birjand was also as high as 5.34 cases per 1000 live births (23).…”
Section: Discussionmentioning
confidence: 99%